MULTI-ATTRIBUTE ANALYSIS OF ORCHARD ACCORDING TO THE INTEGRATED PRODUCTION CONCEPT - Maksimović, Aleksandar; Grgić, Zoran; Ćejvanović, Ferhat (Economics of Agriculture, 2017)
Integrated fruit production (IFP) is an economical, high-quality fruit production which prioritizes ecologically acceptable means of production, which minimize side-effects aiming to increase environment conservation and human health. Following the market demands and increasing production standards, integrated production imposes itself, which is to enable lucrativeness, market competition and ecological acceptability of agricultural products. Introducing and implementing multi-criteria model of decision-making is based on DEXi method (multi-attribute analysis). This method makes selection of the most adequate fruit sort for initiating fruit production. This model of decision-making is based on opinions of experts from the Feld of integrated production. The main criterion in evaluating IFP according to DEXi and expert system are: economic, technological, ecological and socio-political. The result of multi-criteria expert system DEXi have shown that the plum fruit sort yields the best results according to integrated production concept and can be recommended as the first planting alternative. The second alternative recommends apple while the third one recommends pear.